Tax Revenue, Capital Market Performance and Foreign Direct Investment in an Emerging Economy - Emmanuel, Akpokerere Othuke; Eloho, Osevwe-Okoroyibo Elizabeth; Dabor, Alexander Olawumi; Dabor, Eyesan Leslie; Aggreh, Meshack (International Journal of Economics and Financial Issues, 2024)
The study examines tax revenue, capital market performance and foreign direct investment (FDI) in Nigeria. The broad objective of this study is to find out the relationship between tax revenue, capital market performance and FDI in Nigeria. The study adopted a longitudinal research design and covers a period of 1994-2021. Secondary data were obtained from annual report and bulletins of the Central Bank of Nigeria. This study employed the ADF and Philips-Perron (PP) unit root test, panel Johansen cointegration test, VAR model, dynamic ordinary least square regression, full modified ordinary least regression and pairwise granger. The findings amongst others revealed that; value added tax has a bidirectional relationship with foreign direct investment in Nigeria; company income tax has no significant relationship with foreign direct investment in Nigeria; custom and exercise duty has a unidirectional relationship with foreign direct investment in Nigeria; stock market capitalization has no significant relationship with foreign direct investment in Nigeria. Based on the findings, the study recommended amongst others that policy makers should concentrate effort on long run policies that will stimulate capital market development in Nigeria, Also, a healthier and more robust friendly foreign investment policies should be created and maintained and the government should partners with foreign investors to enhance capital market development in Nigeria.